Hepatitis C virus genotypes in hemodialysis patients in the Federal District, Brazil Genótipos do vírus da hepatite C em pacientes em hemodiálise no Distrito Federal, Brasil - Regina M.S. Amorim; Tainá Raiol; José E. Trevizoli; Francisco A. R. Neves; Cláudia R.F. Martins; Regina M.B. Martins (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Hepatitis C virus (HCV) genotypes and subtypes were determined in hemodialysis patients in the Federal District, Brazil, by sequencing of the 5' noncoding (NC) and nonstructural 5B (NS5B) regions. From 761 patients, 66 anti-HCV-positive samples were tested for HCV RNA. All 51 HCV RNA-positive samples by PCR of the 5' NC region were genotyped as genotypes 1 (90.2%) and 3 (9.8%). Subtype 1a (82.3%) was the most prevalent, followed by subtypes 3a (9.8%), 1b (5.9%) and 1a/1b (2.0%). Forty-two samples could be amplif﻿﻿ied and genotyped in the NS5B region: 38 (90.5%) as genotype 1, subtypes 1a, and 8 (9.5%) as genotype 3, subtype 3a. For the 42 samples sequenced in both regions, the genotypes and subtypes determined were concordant in 100% and 95.2% of cases, respectively. Two samples presented discrepant results, with the 5' NC region not distinguishing correctly the subtypes 1a and 1b. These findings indicate that the HCV genotype 1, subtype 1a, is the most prevalent among hemodialysis patients in the Federal District, Brazil. Os genótipos e subtipos do vírus da hepatite C (HCV) foram determinados em pacientes em hemodiálise no Distrito Federal, Brasil, pelo sequenciamento das regiões 5' não codificante (NC) e não estrutural 5B (NS5B). De 761 pacientes, 66 amostras anti-HCV positivas foram testadas para RNA-HCV. Todas as 51 amostras RNA-HCV positivas por PCR para a região 5' NC foram genotipadas como dos genótipos 1 (90,2%) e 3 (9,8%). O subtipo 1a (82,3%) foi o mais prevalente, seguido pelos subtipos 3a (9,8%), 1b (5,9%) e 1a/1b (2,0%). Quarenta e duas amostras puderam ser amplificadas e genotipadas na região NS5B: 38 (90,5%) como genótipo 1, subtipo 1a, e 8 (9,5%) como genótipo 3, subtipo 3a. Para as 42 amostras sequenciadas nas duas regiões, os genótipos e subtipos determinados foram concordantes em 100% e 95,2% dos casos, respectivamente. Duas amostras apresentaram resultados discrepantes, sendo que a região 5' NC não diferenciou corretamente os subtipos 1a e 1b. Estes achados indicam que o genótipo 1, subtipo 1a, do HCV é o mais prevalente em pacientes em hemodiálise no Distrito Federal, Brasil.